Interactions among amino acid transport systems in snail Helix aspersa intestine (Revista Española de Fisiología, 1987)
Interactions among the transport of diverse amino acids in everted intestine of snail Helix aspersa have been studied.The uptake of 0.5 mM methionine is clearly inhibited by high concentrations (40 mM) of leucine, and not by proline or lysine, whereas the last two amino acids inhibit cycloleucine uptake.Methionine strongly inhibits proline and lysine uptake, which is significantly inhibited by their analogs hydroxiproline and arginine, respectively.Results suggest that in Helix intestine the transport systems for basic amino acids and iminoacids are shared with high affinity by methionine whereas the neutral amino acids transport systems do not seem to be shared, or are so very weakly, by the basic ones or by the imino acids.